1. The problem statement, all variables and given/known data x*e^(y/x) + y dx = xdy, y(1) = 0 2. Relevant equations 3. The attempt at a solution To solve, I divide everything by x dx to put everything in terms of v. e^v + v = dy/dx dy/dx = x dv/dx + v e^v + v = x dv/dx + v e^v = x dv/dx e^v / dv = x/dx Flip both sides. e^-v dv = 1/x dx Integrate both sides -e^-v = ln|x| + c -e^(-y/x) = e^(ln|x| + c) -e^(-y/x) = x * e^c -e^(-y/x) = cx ln(-e^(-y/x)) = ln(cx) ln(e^(x/-y)) = ln(cx) -x/y = ln(cx) 1/y = -ln(cx)/x y = -x/(ln(cx)) Is that the correct explicit form? Would it make it easier if I used the initial condition to find c, and then attempted to put it in explicit form, or not?